Influence of Quality of Nursing Work Life on Nurses’ Turnover Intention: the Mediating Effect of Organizational Commitment (Medico Legal Update, 2020)
The top priority of this study was to identify how nurses’ organizational commitment (OC) serves as amediating factor between Quality of Nursing Work Life (QNWL) and turnover intention (TI) among Koreannurses. Three hundred thirteen registered nurses working in hospitals participated in this study. Mediatingeffect analysis was conducted to identify the relationship between QNWL, OC, and TI. The results revealedsignificant correlations between variables. OC showed a perfect mediating effect in the relationship betweenQNWL and TI. The results suggest that nurses’ QNWL has a significant influence on the TI, which ismediated via OC.